Acquired Esophageal Strictures in Children: Morphometric and Immunohistochemical Analyses. (March 2022) - Collins, Margaret H.; Alexander, Eileen S.; Martin, Lisa J.; Grotjan, Tommie M.; Mukkada, Vincent A.; Sheil, Amy; Abonia, Juan P.; Putnam, Philip E.; Rothenberg, Marc E.
Background: Esophageal strictures (ES) in children are not well characterized pathologically. We report unique histopathologic analyses of resected acquired ES and control esophagi (CE). Methods: Muscle layer thicknesses were measured in intact well-oriented areas; inflammatory cells were counted in the most inflamed high power field (hpf). Sections were stained with relevant antibodies. Results were expressed as median, lower and upper quartiles. Wilcoxon Rank Sums non-parametric test was used to compare groups; P ≤ 0.05 was considered significant. Results: All ES (N = 10) showed focal replacement of lamina propria, muscularis mucosa and submucosa by actin+ fibers emanating from muscularis propria. Compared to CE (N = 8), ES displayed significantly thickened muscularis mucosa and propria, and increased mast cells (tryptase- and chymase-positive), and eosinophils in muscle layers (all P ≤ 0.01). Matrix proteins periostin and fibronectin were identified in the muscle layers of CE, and in the extracellular matrix in areas of disrupted architecture in ES. Conclusions: Compared to CE, acquired ES in children show significant structural alterations, including obliterative muscularization, inflammatory cell mural infiltrates, and extracellular matrix protein deposits. Therapies targeting connective tissue expansion, mast cells, eosinophils and inflammation may be beneficial to treat ES.